Pengaruh Reward Punishment dan Pelatihan Kerja terhadap Kinerja Karyawan pada PT. Sumber Berkat Sempurna (Otomedia) Jakarta Selatan - Savannah Nurhaliza; Lilis Suryani (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstract. This study aims to examine the effect of reward–punishment and job training on employee performance at PT. Sumber Berkat Sempurna (Otomedia), South Jakarta, both partially and simultaneously. The research method used is a quantitative approach. The sampling technique employed the Slovin formula, resulting in a sample of 53 respondents. Data were collected through the distribution of questionnaires. The data analysis techniques included validity tests, reliability tests, classical assumption tests, simple and multiple linear regression analyses, correlation analysis, coefficient of determination, and hypothesis testing. The results show that, partially, reward–punishment has a significant effect on employee performance, as indicated by a tcount value of 8.018 which is greater than the ttable value of 1.675, with a significance level of < 0.001. Job training also has a significant effect on employee performance, as evidenced by a tcount value of 5.640 which is greater than the ttable value of 1.675, with a significance level of < 0.001. Simultaneously, reward–punishment and job training have a significant effect on employee performance, as indicated by an Fcount value of 33.019 which is greater than the Ftable value of 3.18, with a significance level of < 0.001. The coefficient of determination shows that reward–punishment and job training jointly contribute 53.7% to employee performance, while the remaining 46.3% is influenced by other factors outside this study. Therefore, it can be concluded that reward–punishment and job training have a significant effect on employee performance at PT. Sumber Berkat Sempurna (Otomedia).